STUDI KASUS IMBANGAN ANGKUTAN SEDIMEN DI KALI PUTIH - Rizal Gunawan, Darmono (Universitas Negeri Yogyakarta, 2015)
ABSTRACTThis study aims to find out the volume of a flood plan and balance between sediment raised in themining of sand and sediment that comes in the time of flooding in kali Putih river’s area regional ofSrumbung. The method of study is using observation method, interview method, and literaturemethod. Hydrology data used in this study is map kali Putih river, map rain stasiun, and gradationof sand grains. To calculate the volume of a flood plan is using the rational method, weduwenmethod, and hasper method. And to calculate sediment transport using Mayer, Peter and Mullerformulation. The calculation based on 5 rain station Argomulyo, G.maron, Ngepos, Babadan, andKaliadem station using (1) Rasional, (2) Weduwen and (3) Hasper to 5 year reissue period are: (1)233,94 m3/sec, (2) 80,67 m3/sec, (3) 129,48 m3/sec. Tthe result of the calculation of sedimenttransport using Meyer, Petter and Muller formulation produces sediment transport base for theentire widht of the river of 4,66 m3/second, and base sediment transport for 1 hour of 16776m3.From the result of mining sediment of Srumbung area is 492750 m3/year. So the mining wasdone in Srumbung for 1 year is 492750 m3can be offset by during floods for 11,54 hours resultingheaps of 493214,4 m3.